Phenotypic, Genomic and Functional Characterization Reveals No Differences between CD138(++) and CD138(low) Subpopulations in Multiple Myeloma Cell Lines - Paíno, Teresa (Public Library of Science, 2014)
Despite recent advances in the treatment of multiple myeloma (MM), it remains an incurable disease potentially due to the presence of resistant myeloma cancer stem cells (MM-CSC). Although the presence of clonogenic cells in MM was described three decades ago, the phenotype of MM-CSC is still controversial, especially with respect to the expression of syndecan-1 (CD138). Here, we demonstrate the presence of two subpopulations - CD138(++) (95–99%) and CD138(low) (1–5%) - in eight MM cell lines. To find out possible stem-cell-like features, we have phenotypically, genomic and functionally characterized the two subpopulations. Our results show that the minor CD138(low) subpopulation is morphologically identical to the CD138(++) fraction and does not represent a more immature B-cell compartment (with lack of CD19, CD20 and CD27 expression). Moreover, both subpopulations have similar gene expression and genomic profiles. Importantly, both CD138(++) and CD138(low) subpopulations have similar sensitivity to bortezomib, melphalan and doxorubicin. Finally, serial engraftment in CB17-SCID mice shows that CD138(++) as well as CD138(low) cells have self-renewal potential and they are phenotypically interconvertible. Overall, our results differ from previously published data in MM cell lines which attribute a B-cell phenotype to MM-CSC. Future characterization of clonal plasma cell subpopulations in MM patients' samples will guarantee the discovery of more reliable markers able to discriminate true clonogenic myeloma cells.